PENGARUH UKURAN KAP, PERGANTIAN MANAJEMEN DAN UKURAN PERUSAHAAN TERHADAP AUDITOR SWITCHING (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Bernard Pryono, 15.05.62.0015; Badjuri, Achmad (Students Journal of Accounting and Banking, 2018)
This study aims to examine the effect of KAP Size, Change of Management, and Company Size Against Auditors Switching of mining companies listed on the Indonesia Stock Exchange (IDX). This study uses a sample of mining manufacturing companies listed on the Stock Exchange from 2014 to 2016 using 36 sample companies for 3 consecutive years. This study used multiple regression analysis tools. Based on the results on the results of research conducted showed that the size of KAP, the change of management, and firm size are not significant to the switching auditor.Keywords: KAP Size, Change of Management, Company Size, Switching Auditor.